(untitled) (Minerva, 2025)
This article advances a comparative study between Ovid’s Tristia and the potpourri La oveja negra (2024) written by Antonio Martínez Ares, based on an analysis of the topic of exile as an aesthetic, symbolic and literary category. Whilst the article does not claim a direct relationship between both pieces, it explores the structural, thematic and rhetorical analogies that arise between the experience of the poet exiled in Tomis and that of the dissident subject speaking from the margins in the context of the Carnival. After a brief theoretical review of exile as a literary motif —from antiquity to contemporary literature— the study analyses how both texts shape a poetics of uprootedness, a break- away from the order and an identity resistance. At the same time, it supports the literary value of the Cádiz Carnival, and in particular of the comparsa, as a legitimate form of lyrical and critical expression in line with traditions deep-rooted in Western culture.